The effect of pDNA-Buforin II on the expression changes of lncRNAs PCA3, PCAT1, PRNCR1, GAS5 in prostate cancer - Fatemeh Dehkhodaei; Abbas Doosti (Advances in Cancer Biology - Metastasis)
Background: This work aims to analyze the alterations in the levels of PCA3, PCAT1, PRNCR1, and GAS5 long non-coding RNAs (lncRNAs) after the activation of pDNA-buforin II in PC3 cancer cells. Materials and methods: The synthetic nucleic acid sequence of buforin II was included in the pcDNA3.1(+) Mammalian Expression Plasmid. The accuracy of cloning was assessed by using PCR and enzyme digestion techniques. The vectors were transfected into cells utilizing LipofectamineTM2000. The PC3 cancer cells were evaluated using flow cytometry and wound healing analysis. The expression levels of lncRNAs and apoptotic genes were assessed utilizing real-time PCR, with a significance threshold of P < 0.05. Results: The recombinant plasmid containing the pDNA-buforin II vector was successfully generated, and the gene sequence demonstrated complete uniformity (100 % similarity) with the buforin II gene. The transfection efficiency of PC3 cells was 79 %. The results are quantified utilizing the growth inhibition 50 % (GI50) parameter, representing the concentration of pDNA-buforin II required to halt 50 % of cell growth. The percentages of early apoptosis, late apoptosis, necrosis, and viable PC3 cells in the pDNA-buforin II group were 23.30 %, 12.70 %, 3.9 %, and 60.10 %, respectively. The RT-PCR study demonstrated that the presence of pDNA-buforin II in PC3 cells decreased the transcription of PCA3, PCAT1, and PRNCR1 lncRNAs compared to the control group treated with PBS. Furthermore, it enhanced the transcription of GAS5 lncRNA. The findings demonstrated a significant upregulation of transcription factors in programmed cell death after treatment with pDNA-buforin II (∗∗P < 0.01). Conclusions: According to the results of this study, it can be inferred that pDNA-buforin II can modify the transcription of genes in PC3 cancer cells, specifically about lncRNAs involved in cell apoptotic pathways. The pDNA-buforin II molecule has promising anticancer capabilities and can trigger apoptosis in cells.